FORMULATION AND EVALUATION OFENTERIC COATED PELLETS OF RIFAMPICIN AND ISONIAZID WITH IMPROVED RIFAMPICIN STABILITY - Krishna T, Vamshi; Sreenivasa Reddy, M. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The aim of the present study is to formulate and evaluate enteric coated pellets of Rifampicin and Isoniazid with improved Rifampicin stability in invitro conditions. Methodology: Two different capsule formulations of these drugs were prepared. Formulation-I contains immediate release uncoated pellets of Rifampicin and Isoniazid. Formulation-IIcontains immediate release enteric coated pellets of Rifampicin and Isoniazid. These pellets were evaluated for various physicochemical parameters. Enteric coating was mainly done to prevent the release of these drugs in acidic medium and to improve the stability of Rifampicin by preventing its interaction with Isoniazid in acidic medium. Dissolution studies for both these formulations were performed and the cumulative percentage drug release for Rifampicin was calculated. Results: The cumulative percentage drug release for Rifampicin was found to be around 81% in formulation-I whereas it has been increased to 89% in formulation-II. Conclusion: This study proves that Rifampicin interacts with Isoniazid and undergoes degradation to a significant extent in acidic medium. This interaction and degradation can be reduced and the stabilityof Rifampicin can be enhanced by formulating them as enteric coated dosage forms. Keywords: Rifampicin, Isoniazid, Enteric coating,pellets